Emerging Prospects for the Study of Colorectal Cancer Stem Cells using Patient-derived Organoids - Ding, Ling; Yang, Yuning; Lu, Qin; Cao, Zhiyun; Weygant, Nathaniel (Current Cancer Drug Targets, 2022)
Human colorectal cancer (CRC) patient-derived organoids (PDOs) are a powerful ex vivo platform to directly assess the impact of molecular alterations and therapies on tumor cell proliferation, differentiation, response to chemotherapy, tumor-microenvironment interactions, and other facets of CRC biology. Next-generation sequencing studies have demonstrated that CRC is a highly heterogeneous disease with multiple distinct subtypes. PDOs are a promising new tool to study CRC due to their ability to accurately recapitulate their source tumor and thus reproduce this heterogeneity. This review summarizes the state-of-the-art for CRC PDOs in the study of cancer stem cells (CSCs) and the cancer stem cell niche. Areas of focus include the relevance of PDOs to understanding CSC-related paracrine signaling, identifying interactions between CSCs and the tumor microenvironment, and modeling CSC-driven resistance to chemotherapies and targeted therapies. Finally, we summarize current findings regarding the identification and verification of CSC targets using PDOs and their potential use in personalized medicine.
Keywords: personalized medicine